A LONG STRIDE INTO RUSSIA’S FOOD SECURITY AND SOVEREIGNTY - Abel Josafat Manullang (Journal of International Relations, 2023)
Food security, and the following food sovereignty, is an important part of a state’s survival in the international system. Such is the case for Russia, another growing power in the post-Cold War era. How a state maintains its food security is an interesting point to look into, hence this research is done. The guiding points that would guide the article would be the food security of Russia, the food sovereignty movement in the country, along with how the ongoing Russia-Ukraine conflict affects Russia’s food security.The writing uses the concept of food security and food sovereignty that would be analyzed through the qualitative method of analysis. For the case of Russia’s food security, it’s found that the meat and industry, under Russia’s Food Security Doctrine, play an important role to maintain food security. The movement for food sovereignty in Russia on the other hand is present but they do not take the form shown in other countries as a means to conform with the domestic condition of Russia. Moreover, the ongoing conflict between Russia and Ukraine not only affects the global food supply but also the domestic food production within Russia.